TRACE ELEMENT DISTRIBUTIONS IN THE CHALCOPYRITE WALL OF A BLACK SMOKER CHIMNEY: INSIGHTS FROM LASER ABLATION INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY (LA-ICP-MS) - Butler I.B.; Nesbitt R.W. (My University, 1999)
The thin walls of young black smoker chimneys experience steep physico-chemical gradients during active venting of hydrothermal fluid, and these gradients control trace element precipitation within those walls. Here, we utilise a combination of high sensitivity ICPMS and UV laser ablation (resolution of better than 30 μm) to demonstrate the existence of non-random V, Ag, In, Te, Ba, Au, Pb and U distributions within the chalcopyrite wall of an immature black smoker chimney. The data are the first of their kind to be produced for black smoker chimney walls. Distributions of In and Te are attributed to preferential incorporation into lattices at elevated temperature. Enrichments of U and V derived from seawater are the product of redox immobilisation on sulphide surfaces. The distributions of Au, Ag, Pb and Ba may be related to interactions at the hydrothermal fluid-seawater mixing front; however, comparison of distribution data with reaction-transport models of chimney walls suggest a possible pH control on precipitation. These data illustrate the power of the LA-ICP-MS method, and such spatially resolved data have the potential to constrain models of element precipitation both in chimneys and in associated mounds.
Keywords: TRACE ELEMENTS; SULFIDES; HYDROTHERMAL VENTS; LASER METHODS; INDUCTIVELY COUPLED PLASMA METHODS; MASS SPECTROSCOPY